Confidence Indicators and Their Relationship to Changes in Economic Activity - Santero, Teresa (OECD Economics Department Working Papers, 1996)
This paper examines the usefulness of consumer and business surveys in assessing the cyclical position of the economy and for forecasting output movements. To that effect, after a brief review of the nature of sentiment measures, the empirical relationship between confidence indicators and output components is explored. Graphical examination, correlation analysis and Granger causality tests are used to asses that relationship. The paper finds that sentiment measures obtained from business surveys provide valuable information for the assessment of the economic situation and forecasting. However, the relationship between sentiment indicators and output varies considerably across countries and sentiment measures. It is also found that consumer confidence indicators are much less useful than business confidence indicators for economic analysis due to their much looser relationship with output movements ...